Moderators of the relationship between organizational injustice and employee stress - Johnson, Rachel M., author; Byrne, Zinta, advisor (Colorado State University. Libraries, 2008)
Although there have been a few notable research studies illustrating the relationship between organizational injustice and stress in the workplace, hardly any researchers have investigated potential moderators of the injustice-stress relationship. I first present an overall theoretical model explaining the relationship between injustice and stress, and then empirically test a portion of the model. Specifically, the empirical investigation examined possible individual difference and situational moderators of the relationship between organizational injustice and perceived stress. Approximately 300 participants, undergraduate students, were recruited from a Western university and given measures of belief in ultimate justice, sensitivity to befallen injustice, equity sensitivity, four types of organizational injustice (distributive, procedural, interpersonal, and informational), social support, perceived stress, and strain in order to test the hypotheses derived from the theoretical model. Results showed that perceived stress fully mediated the relationships between distributive and procedural injustice and strain, and partially mediated the relationship between interpersonal injustice and strain. Also, perceived supervisory support buffered the effects of procedural and interpersonal injustice on stress.
Keywords: employee stress; fairness; organizational injustice; organizational justice; sensitivity to befallen justice; stress; supervisory support; experimental psychology